2012
DOI: 10.1016/j.brainres.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The atypical antidepressant mirtazapine attenuates expression of morphine-induced place preference and motor sensitization

Abstract: Opioid abuse and dependence remains prevalent despite having multiple FDA-approved medications to help maintain abstinence. Mirtazapine is an atypical antidepressant receiving attention for substance abuse pharmacotherapy, and its action includes alterations in monoaminergic transmission. As monoamines are indirectly altered by opioids, the current investigation assessed the ability of mirtazapine to ameliorate morphine-induced behaviors. Conditioned place preference (CPP) is a behavioral assay wherein a rewar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
2
14
1
1
Order By: Relevance
“…5, chronic mirtazapine infusion did not alter the improvements in akinesia provided by PPX; however, PPX-enhanced risk-taking was attenuated (albeit, modestly). This trend is in keeping with the ability of mirtazapine to reduce motivated behaviors sustained by abused drugs in rats and humans [1822,24,45] and ICSS-mediated decision-making in rats [46]. Outcomes also indicate that the systems engaged by mirtazapine may be more relevant to ICD than motor function.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…5, chronic mirtazapine infusion did not alter the improvements in akinesia provided by PPX; however, PPX-enhanced risk-taking was attenuated (albeit, modestly). This trend is in keeping with the ability of mirtazapine to reduce motivated behaviors sustained by abused drugs in rats and humans [1822,24,45] and ICSS-mediated decision-making in rats [46]. Outcomes also indicate that the systems engaged by mirtazapine may be more relevant to ICD than motor function.…”
Section: Discussionsupporting
confidence: 58%
“…Mirtazapine was dissolved in 1N HCl, diluted with sterile water, brought to 5.5–6.0pH with 1N NaOH and delivered as 5mg/kg/day. We previously determined in rats that this dose of mirtazapine does not alter locomotor function [18] but is sufficient to reduce several measures of drug reward-motivated behavior [1822]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5, 6 However, another study showed that the expression of morphine-induced CPP was attenuated by pretreatment of mirtazapine (an atypical antidepressant). 35 The data showed that nortriptyline did not affect the acquisition of morphine-induced CPP in naïve rats, similar to the finding in a previous report using a combination of imipramine and morphine. 7 All of these studies used naïve rats and the differences regarding the effect of antidepressant on morphine-induced CPP may be related to different antidepressants (e.g., selective serotonin reuptake inhibitor versus selective norepinephrine reuptake inhibitor).…”
Section: Discussionsupporting
confidence: 89%
“…Mirtazapine is an atypical antidepressant with a complex pharmacological profile that includes antagonism at 5-HT 2A/2C receptors (De Boer, 1995;Wikstrom et al, 2002). Mirtazapine attenuates various behaviors motivated by abused drugs, including methamphetamine (Herrold et al, 2009;Voigt et al, 2011;Graves and Napier, 2011;Voigt and Napier, 2011) and morphine (Graves et al, 2012a) in rats, and reduces cocaine intake in humans (Graves et al, 2012b). We recently revealed that mirtazapine reduces the capacity of the dopamine D2/D3 receptor agonist, pramipexole, to induce risky decision-making by rats performing a probability discounting task (Holtz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%